GLOSSÁRIO DE CULTURA DE TECIDOS DE PLANTAS - PORTUGAL PINTO DE CARVALHO, ANA CRISTINA; TORRES, ANTONIO CARLOS; BOLACEL BRAGA, EUGÊNIA JACIRA; PINTO DE LEMOS, EURICO EDUARDO; VIDIGAL DUARTE SOUZA, FERNANDA; PETERS, JOSÉ ANTONIO; WILLADINO, LILIA; RANGEL CÂMARA, TEREZINHA (Plant Cell Culture & Micropropagation - ISSN 1808-9909, 2016)
vide artigo